2014
DOI: 10.1371/journal.pone.0089563
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetics Induce Apoptosis in Human Thyroid Cancer Cells through the Mitogen-Activated Protein Kinase Pathway

Abstract: Local anesthetics are frequently used in fine-needle aspiration of thyroid lesions and locoregional control of persistent or recurrent thyroid cancer. Recent evidence suggests that local anesthetics have a broad spectrum of effects including inhibition of cell proliferation and induction of apoptosis in neuronal and other types of cells. In this study, we demonstrated that treatment with lidocaine and bupivacaine resulted in decreased cell viability and colony formation of both 8505C and K1 cells in a dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 48 publications
8
108
0
3
Order By: Relevance
“…Chang et al (16) found that lidocaine and bupivacaine may be ideal infiltration anesthetics for breast cancer surgery as they could induce apoptosis of human breast cancer cells at clinically relevant concentrations, and since they demonstrated potential benefits of local anesthetics. Subsequently, after investigating lidocaine and bupivacaine treatment in human thyroid cancer cells, the study also found a significant decrease in cell viability and colony formation in a dose-dependent manner as the result of treatment with lidocaine and bupivacaine at higher concentrations, and suggested that lidocaine and bupivacaine may induce cell apoptosis through the mitogen-activated protein kinase pathway (21). The present study assessed the cytotoxicity of lidocaine at 1 to 10 mM and also found that lidocaine was able to significantly decreased cell viability of MDA-MB-231, PC-3 and ES-2 cells in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 96%
“…Chang et al (16) found that lidocaine and bupivacaine may be ideal infiltration anesthetics for breast cancer surgery as they could induce apoptosis of human breast cancer cells at clinically relevant concentrations, and since they demonstrated potential benefits of local anesthetics. Subsequently, after investigating lidocaine and bupivacaine treatment in human thyroid cancer cells, the study also found a significant decrease in cell viability and colony formation in a dose-dependent manner as the result of treatment with lidocaine and bupivacaine at higher concentrations, and suggested that lidocaine and bupivacaine may induce cell apoptosis through the mitogen-activated protein kinase pathway (21). The present study assessed the cytotoxicity of lidocaine at 1 to 10 mM and also found that lidocaine was able to significantly decreased cell viability of MDA-MB-231, PC-3 and ES-2 cells in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 96%
“…Cleaved caspase-3, the active form of caspase-3, was the capital cleavage enzyme in apoptosis (13). Apoptosis was characterized by the nuclear DNA degradation in response to a variety of apoptotic stimuli (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…It seems to be unrelated to the sodium-channel blockade (8)(9)(10), while in other reports local anesthetics work in the manner of inhibiting the activity of sodium channels (11,12). Previous study has suggested that local anesthetics could induce apoptosis in human thyroid cancer cells, which is associated with mitogen-activated protein kinase (MAPK) pathways (13). Another report has suggested that inhibition of MAPK pathways protects against local anesthetics-induced neurotoxicity (14).…”
Section: Introductionmentioning
confidence: 99%
“…Colony formation assay was performed as previously described (Chang et al 2014). In brief, BCPAP (1000 cells/ well) and K1 cells (500 cells/well) were seeded into six-well plates, allowed to adhere for 24 h, and treated with isotype control, recombinant human MIF (200 ng/ml) or anti-CD74 antibody (5 mg/ml) from day 2.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%